Oral hygiene guidance for home patients: Experience report (Research, Society and Development, 2025)
The present study seeks to address the practice of oral hygiene in home patients, registered in the Unified Health System monitoring sector in the city of Rolim de Moura - RO. Therefore, this work aimed to report the experience of dentistry students in developing activities to promote the oral health of the target audience, through lectures and model demonstrations on the topic. During the present study, it was possible to characterize bedridden patients according to their pathology and promote oral health through home visits. It was observed that the performance of the Oral Health Team aimed at this public is still low and almost non-existent, making further studies and implementation of public policies on this topic necessary. It is concluded that home visits can be another tool for expanding access to oral health care for the bedridden population and promoting the creation of bonds between health professionals and the family.